2021
DOI: 10.1016/j.eclinm.2021.100990
|View full text |Cite
|
Sign up to set email alerts
|

The effect of smoking status on efficacy of immune checkpoint inhibitors in metastatic non-small cell lung cancer: A systematic review and meta-analysis

Abstract: Background: It remains uncertain whether smoking status can effect efficacy of immune checkpoint inhibitors (ICIs) in metastatic non-small cell lung cancer (NSCLC). We performed a meta-analysis to address this issue.Patients and methods: PubMed, Embase, Cochrane Library, Web of Science, and international meetings were searched until April 1, 2021, for phase 2 and 3 randomized controlled trials (RCTs) which compared ICIs with chemotherapy (CT) and reported overall survival (OS) and/or progression-free survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 55 publications
2
23
0
Order By: Relevance
“…Our results are supported by other studies. A recent meta-analysis by Dai et al [ 100 ] found that ICI monotherapy and dual ICIs improved survival in ever smokers but not never smokers, regardless of PD-L1, and that the addition of chemotherapy was able to improve survival for both groups. Several real-world studies and analyses further support these observed associations [ 101 , 102 , 103 ].…”
Section: Future Directions To Understanding Tobacco Use and Ici Outcomesmentioning
confidence: 99%
“…Our results are supported by other studies. A recent meta-analysis by Dai et al [ 100 ] found that ICI monotherapy and dual ICIs improved survival in ever smokers but not never smokers, regardless of PD-L1, and that the addition of chemotherapy was able to improve survival for both groups. Several real-world studies and analyses further support these observed associations [ 101 , 102 , 103 ].…”
Section: Future Directions To Understanding Tobacco Use and Ici Outcomesmentioning
confidence: 99%
“…Further trials are needed as there are no RCTs yet that specifically focus on the value of immunotherapy in the subgroup of ALK-positive NSCLC, probably due to small patient numbers. In contrast, there are numerous RCTs that have shown the lacking benefit of immunotherapy in never smokers [29,30]. The patient in this case report stopped smoking twenty years ago and had only a ten pack-year history of tobacco smoking.…”
Section: Discussionmentioning
confidence: 76%
“…Overall, considering that a single biomarker, even though it may be crucial for posing the indication for a specific agent, is not able to catch the complexity of a patient, all known prognostic and predictive factors should be considered during the pretreatment evaluation (Fig. 2), including some parameters that are fairly easy to assess, such as the tumor burden, both radiologically and laboratory evaluated [103], the ECOG PS [104] and the tobacco smoking status [105]. Among immunoinflammatory indexes, the Lung Immune Prognostic Index (LIPI) score [106,107] was retrospectively tested in a cohort of 191 patients aged ≥ 70 with advanced tumors (27% NSCLC) treated with ICBs.…”
Section: Discussionmentioning
confidence: 99%